The Relationship Between Diabetes Mellitus and Cataract Incidence at the JEC Orbita Makassar Main Eye Clinic - Eka Uthami Tonang; Zulfikri Khalil Novriansyah; Ratih Natasha Maharani; Marlyanti Nur Rahmah; Ariyanie Nurtania (PSPP JOURNALS, 2026)
Diabetes Mellitus (DM) is a chronic non-communicable disease with an increasing incidence rate and the potential to cause various complications, including ocular disorders such as cataracts. Cataracts are the leading cause of blindness worldwide and occur more frequently in DM patients due to chronic hyperglycemia that accelerates lens opacity. This study aims to determine the relationship between diabetes mellitus and the occurrence of cataracts at the JEC Orbita Eye Clinic in Makassar. This is an observational analytic study with a cross-sectional design using a quantitative approach. Data were obtained from patient medical records in January 2025-December 2025. The sample was taken using a total sampling method with a total of 250 patients. Data were analyzed univariately and bivariately using the Chi-Square test. Out of 250 patients, the largest age group was ≥ 60 years (36.8%), followed by 45–59 years (33.2%). The gender distribution was balanced between males and females (50% each). A total of 205 patients (82%) had diabetes mellitus. The Chi-Square test showed a significant association between diabetes mellitus and cataract (p < 0.05). Cataract was more commonly found in adult and elderly patients with a balanced gender proportion. Most cataract patients had diabetes mellitus, and there was a significant association between diabetes mellitus and cataract.